Patient satisfaction with the quality of healthcare services at selected major outpatient clinics at Sultan Ahmad Shah Medical Centre Kuantan Pahang - Che' Man, Mohamad; Che Alhadi, Shahidah; Yusof, Muhammad Zubir; Mohd Arifin, Siti Roshaidai; Mohd Razib, Mohd Zhafri; Amiruddin, Salman (IIUM Press, 2024)
INTRODUCTION: Patient satisfaction is a key factor in determining any gaps or inadequacies in the healthcare provider's services. This study aimed to measure the level of patient satisfaction and its associated factors towards the healthcare service of outpatient clinics in Sultan Ahmad Shah Medical Centre (SASMEC), IIUM, Kuantan, Pahang. MATERIALS AND METHODS: A total of 1050 patients were recruited from internal medicine, paediatrics, surgery, obstetrics and gynaecology, orthopaedics, and psychiatry clinics between February 2021 and February 2022. A questionnaire was administered which consists of two parts: one that covers patients’ sociodemographic data and the other that assesses the patients’ level of satisfaction with the healthcare services using the Malay-validated Short-Form Patient Satisfaction Questionnaire (PSQ-18). RESULTS: The mean overall satisfaction level was 3.94 ± 0.46, with the highest mean scores in the interpersonal manners (4.2 ± 0.64) and communications (4.26 ± 0.56) domains. From the multivariate analysis, it was found that those patients in the lower income group (B40) were more satisfied with the quality of the healthcare services (B=0.172, 95% CI=0.08, 0.263) compared to the middle-income group. Being a student (B=-0.202, 95% CI=-0.296, -0.108) and having a follow-up treatment visit (B=-0.082, 95% CI=-0.156, -0.008), were significantly associated with lower satisfaction levels as compared to their counterparts. CONCLUSION: Overall, patients who attended SASMEC were satisfied with the service provided. Continuous service improvement aimed at patients’ household income, occupation and purpose of visit may help SASMEC enhance its service in the future.